Use of allogeneic platelet-rich plasma for the treatment of autoimmune ocular surface disorders: case series - Mancini, Maura; Postorino, Elisa Imelde; Gargiulo, Ludovica; Aragona, Pasquale (Frontiers in Ophthalmology, 2023)
Purpose To assess the effectiveness of topical allogeneic platelet-rich plasma (PRP) eye drops for the treatment of symptoms and clinical signs in patients with severe dry eye disease as a secondary condition caused by Sjögren’s syndrome (SS). Design Case series and literature review. Methods Six eyes from three consecutive patients with severe dry eye from SS were evaluated. The eyes were treated with allogeneic topical PRP eye drops, with one drop applied six times daily for 3 months. A post-treatment follow-up evaluation was conducted 3 months after treatment suspension. We evaluated subjective symptoms, visual acuity, tear breakup time, the results of Schirmer’s I test, fluorescein corneal and conjunctival staining, and corneal sensitivity. Results The symptoms and visual acuity improved significantly in all patients. There was a significant improvement in corneal sensitivity and a decrease or disappearance of fluorescein corneal staining. Conclusion The treatment with allogenic PRP eye drops of patients with SS-related severe dry eye disease has proven to be very effective, with an improvement in symptoms and main clinical signs.